Future‐proofing synthetic biology: educating the next generation. Issue 2 (17th June 2019) - Hallinan, Jennifer S.; Wipat, Anil; Kitney, Richard; Woods, Simon; Taylor, Ken; Goñi‐Moreno, Angel
Abstract : Synthetic biology is a relatively young field, although it builds upon disciplines whose roots go back centuries. Recently, its practitioners have tended to move into the field out of interest or by chance, and come from a wide variety of backgrounds. It is also a very fast‐moving field; new protocols, laboratory equipment, computational facilities and algorithms are being developed at a rapid pace. Students who start studying synthetic biology at an undergraduate or postgraduate level will, in the course of their careers, work with technologies as yet undreamt of, and will do so mostly in the context of highly interdisciplinary teams. In this study, the authors identify some of the key areas required for the education of new synthetic biologists to equip them with both adequate background and sufficient flexibility to tackle these challenges and therefore to future‐proof synthetic biology.